Polarity and Bonding Properties of Cluster NiCo2S4 - ZENG Xinyu; FANG Zhigang; JING Runtian; WANG Qian; MAO Zhilong; ZHU Yiwen (Journal of Harbin University of Science and Technology, 2023)
Based on density functional theory (DFT),the clusterNiCo2S4was optimized at B3LYP/Lan12dz level in order to determin eleven optimized configurations and analyze their polarity and bonding properties.The results showed that the polarity of configuration 1(3) is the largest and the polarity of configuration 4(3)is the smallest.In the bond length analysis, Ni-Co and Co-Co bonds have antagonistic effect, and Ni-S, Co-S and S-S bonds have synergistic effect. The bonding effect of the same metal atom is the best, and the same nonmetallic atom is the worst.In the bond level analysis, the bond levels of configuration 4(1)and configuration 6(1)are all positive, and the bonding strength is strong.The main chemical bond hybridization modes are obtained by density of states diagram analysis: in the triplet configurations, there are d-d and p-p hybridization in Ni-Co bond and Co-Co bond,p-d hybridization in Ni-S bond and Co-S bond, and p-p hybridization in S-S bond; in the singlet configurations, there is d-d hybridization in Ni-Co bond, Ni-S bond, Co-S bond, Co-Co bond and S-S bond, and p-p hybridization in Ni-Co bond.